DAMPAK PANDEMI COVID-19 TERHADAP PERTUMBUHAN DANA PIHAK KETIGA PADA BANK SYARIAH - Hasan, Hurriah Ali; Mansyur, Saidin; Mustamin, Siti Walida (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The aim of this study is to analyze the impact of contagious of Covid-19 on the growth of Third Party Funds (DPK) in Islamic banks, to see the economic strength during the Covid-19 Pandemic. The analysis was carried out on the financial statements of two Islamic banks, are BNI Syariah and Bank Syariah Mandiri (BSM). By using time series data analysis in the aggregate time of the first semester for the period of January - June and the first month in the second semester in July 2020. The data source is taken from the financial publication monthly report from BNI Syariah and BSM. As a comparison, data for 2018 and 2019 are used in the same month period, so that obtained of the growth trend of DPK in Islamic Bank during normal times and during the Covid-19 pandemic. The results of correlation and comparison analysis, this study found that the Covid-19 pandemic has influenced the trend of public funds in Islamic banks. In choosing fund products at banks, the customer avoid investment risks by reducing deposits in the form of investment funds and prefer Wadiah as safe products. This caused DPK in Islamic banks both BNI Syariah and BSM have significant positive growth for Wadiah and decline in investment funds during the Covid-19 pandemic. This shows that Islamic banking faces financial risks in abnormal situations during the Covid-19 pandemic.